A arquitetura Neogótica no Período da Borracha: um estudo tipológico das construções de Manaus. - Dias, Pollyanna D’Avila Gonçalves (2013)
The Rubber Boom Period provided great cultural and social changes in the city of Manaus and encouraged the inclusion of revivals in public and private architecture. This research analyzed the use of references in the Neogothic buildings of this period and its dialogue with other styles, reflecting the relationship between art and history and the memory of a collectivity. The research was developed from the iconological, typological and symbolic analysis of the buildings: the Reservatório da Castelhana (around 1890), the Chapel of St. John the Baptist Cemetery (1906), the Chapel of the Poor Devil (1897), the Chapel of the Holy House of Mercy (1922), and neogothic fragments of ecletic buildings of the historic center of Manaus.